Bone resorption marker status of pre and postmenopausal malay women in Kelantan and its corresponding risk factors - Hermizi Hapidin,; Hawa Mahmood,; Sakinah Harith, (Universiti Kebangsaan Malaysia, 2013)
Menopause is the most prevalent cause of accelerated bone loss in women. Biochemical markers of bone resorption can be used clinically to predict future bone loss. This study aimed to determine the level of bone resorption markers in healthy pre and postmenopausal Malay women and determine their association with the risk. A total of 150 healthy women were recruited for this study (51 pre and 99 postmenopausal subjects). Data on socioeconomic, lifestyle habit and clinical were gained by personal interview. Fasting serum was collected to measure both C-telopeptide (CTx) and N-telopeptide (NTx) of type 1 collagen. Both markers were highly correlated with each other (r=0.568, p<0.001). Both intra- and inter-assay coefficient of variations (CV) of NTx were higher than those of CTx (8% and 12% vs 6% and 5%). The mean CTx values of pre and postmenopausal subjects were comparable with the expected values (0.2833 (0.1769) ng/mL and 0.4323 (1.851) ng/mL compared with 0.287 and 0.438 ng/mL, respectively). The NTx value for premenopausal subjects were higher than the expected values (15.2 (8.10) compared to 12.6 (3.20) nM BCE). The median was 19.929 nM BCE. The mean CTx and NTx levels of postmenopausal subjects were significantly lower than premenopausal subjects (p<0.05). The risk factors for bone resorption in this population were duration of menopause, marital status, body mass index (BMI), physical activity and education level. In conclusion, postmenopausal women showed a higher bone resorption, indicating higher bone loss. Increasing education and physical activity intervention might be effective to ensure better health in Malaysian older population.